The Use of GLP-1 Receptor Agonists in the Treatment of Obesity in Women with PCOS - Aleksandra Jaroń; Agata Wiklińska; Katarzyna Jastrzębska; Maria Witkowska; Joanna Skotnicka; Karolina Błaszczak; Monika Turek; Klara Wojciechowska; Adrian Borkowski; Mateusz Sawicki (Nicolaus Copernicus University in Toruń, 2024)
Introduction and aim of study: Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders affecting young women. It is diagnosed in individuals who meet 2 of the following 3 criteria: hyperandrogenism, ovarian dysfunction or polycystic ovarian morphology on ultrasound. A common component of this disease is obesity that leads to many serious health complications. This review paper aims to discuss the use of glucagon-like peptide-1 (GLP-1) receptor agonists as a therapeutic option to treat obesity in female patients with PCOS. Materials and Methods: The authors conducted a comprehensive review of the literature available in databases: PubMed and Medline focusing on the terms "PCOS", "GLP-1", "obesity". Results: The first-line treatment of metabolic disorders in the course of PCOS is lifestyle modification. In patients who do not achieve sufficient results pharmacotherapy is recommended. Therapy with GLP-1 receptor agonists shows beneficial effects not only on weight loss, but also on metabolic and endocrine disorders. Studies have proven the superiority of these medications over metformin in the treatment of obesity associated with PCOS. However, the simultaneous use of GLP-1 receptor agonists and metformin may be beneficial for the patients. Conclusions: GLP-1 receptor agonists appear to be a promising therapeutic option in obese women with PCOS according to safety profile and effectiveness proven in studies.